Understanding Consumer Acceptance of Artificial Intelligence in Mobile Banking through Perceived Ease and Usefulness - Winanda Winanda; Antong Antong; Goso Goso (UMSurabaya Publishing, 2026)
This study analyses the factors influencing the adoption of Artificial Intelligence (AI) technology in mobile banking services, focusing on user perceptions regarding ease and benefits in Palopo City. Quantitative methods were used, targeting the complete population of mobile banking service users in the region. Purposive sampling allowed the selection of 210 participants. The results showed that perceived ease of use significantly and positively influenced the adoption of AI functions, while perceived usefulness also showed a significant positive influence. Together, these two factors explained 60.5% of the variation in user acceptance, while the remaining 39.5% was explained by factors outside the scope of this study.